2008
DOI: 10.1073/pnas.0800693105
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of courtship behaviors through the origination of a new gene in Drosophila

Abstract: New genes can originate by the combination of sequences from unrelated genes or their duplicates to form a chimeric structure. These chimeric genes often evolve rapidly, suggesting that they undergo adaptive evolution and may therefore be involved in novel phenotypes. Their functions, however, are rarely known. Here, we describe the phenotypic effects of a chimeric gene, sphinx, that has recently evolved in Drosophila melanogaster. We show that a knockout of this gene leads to increased male-male courtship in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 38 publications
6
66
2
1
Order By: Relevance
“…Five reproductive tissues (F: placenta, ovary, uterus; M: testis, prostate) were detected, with male reproductive expression mainly in testis. Our result is consistent with the association of recent-origin genes with both reproductive expression (23) and reproduction-related behavior (24).…”
Section: Primate-specific Tus Are Preferentially Expressed In the Repsupporting
confidence: 92%
“…Five reproductive tissues (F: placenta, ovary, uterus; M: testis, prostate) were detected, with male reproductive expression mainly in testis. Our result is consistent with the association of recent-origin genes with both reproductive expression (23) and reproduction-related behavior (24).…”
Section: Primate-specific Tus Are Preferentially Expressed In the Repsupporting
confidence: 92%
“…So far only a few Drosophila new genes have received evidence for possible functions, such as Jingwei and Sphinx [26,27]. One of the most striking findings in this study is that MDF1, most likely generated de novo from a non-coding sequence, plays very important roles in two fundamental biological processes, namely mating and growth.…”
Section: Mdf1 Is An Unprecedented Example For the De Novo Originationmentioning
confidence: 66%
“…How these recently originated genes became integrated into pathways and how they conferred a male-related fitness advantage can be deciphered unambiguously only by performing molecular and functional analyses in which these new functions are impaired and the phenotypic consequences monitored. Although still scarce, this type of study has confirmed the contribution of newly evolved genes to sperm production (12), sperm function upon fertilization (13), sperm individualization and motility (14,15), and male courtship (16). Among these case studies, only one (16) involves a species-specific gene.…”
mentioning
confidence: 86%